Planet Mercury may have Retained a Retrograde Satellite - Rawal, J. J.; Keyur, Modha (European Journal of Applied Sciences, 2025)
The limiting direct and retrograde orbits around the planet Mercury have been cal- culated. Synthesizing these concepts with the concepts of Roche limit, synchronous orbit around the planet and the tidal drags acting within it, it is shown here that the planet Mercury might have been able to retain a retrograde satellite. Observers are therefore requested to discover it through infrared telescope of wavelength of a few microns.